Respuestas
Respuesta dada por:
0
Respuesta:
9x+1= 30425+3 (x+2)
9x+1= 30425+3x+6
9x-3x= 30425+6-1
6x= 30430
x= 30430/6
x= 15215/3
Verificación:
9× 15215/3+1= 30425+3 (15215/3+2)
45646= 30425+ 3 (15221/3)
45646= 30425+15221
45646= 45646
Respuesta dada por:
0
Respuesta:
15215/3
Explicación paso a paso:
9x + 1 = (30425)-(-3)(x+2)
9x + 1 = (30425)-(-3x - 6)
9x + 1= 30425 + 3x + 6
9x - 3x = 30425 + 6 - 1
6x = 30430
x = 39430/6 = 15215/3
Preguntas similares
hace 4 años
hace 4 años
hace 4 años
hace 6 años
hace 8 años
hace 8 años